Practical Theology as part of the landscape of Social Sciences and Humanities – A transversal perspective - Müller, Julian (HTS teologiese studies, 2013)
At the University of Pretoria the author, a practical theologian, experiences a fruitful soil for the development of an interdisciplinary process. He referred to concrete examples of cooperation, but used the article to reflect on best practices for the interdisciplinary dialogue. He came to the conclusion that it probably made more sense to talk of Practical-theological alternatives rather than to describe the subject in a single fixed manner of understanding and action. Our goal should rather be to open up the boundaries between Practical Theology, Human, Social and Natural Sciences.